Sustainable Design Education in Taiwan and the Curricular Gap in Policy, Practice, and Pedagogy: A Scoping Review - Jui-Che Tu; Kharisma Creativani (Systems)
This scoping review explores the integration of sustainability into design education within Taiwanese higher education institutions. Taiwan has implemented education reforms and national sustainability policies, yet their integration into creative disciplines like design remains limited. Guided by the PRISMA-ScR framework, this study systematically identified and analyzed sixteen peer-reviewed articles published over the past decade. Thematic analysis and co-occurrence keyword mapping using VOSviewer were used to examine how sustainability is reflected in design curricula. The findings reveal that, while sustainability is frequently addressed in project-based learning and material experimentation, its incorporation remains inconsistent and largely peripheral. Cluster analysis of the literature indicates that national sustainability policies and education initiatives are primarily concentrated in Science, Technology, Engineering, and Mathematics (STEM) fields and general education, with minimal connection to design departments. Design pedagogy in Taiwan emphasizes creativity, iteration, and localized engagement, yet these practices are rarely aligned with policy frameworks or systemic curricular strategies. Barriers include fragmented frameworks and the absence of interdisciplinary collaboration. Despite these limitations, the review identifies promising entry points—mainly through pedagogical innovation and community-based initiatives. This study concludes by calling for policy-aligned, curriculum-integrated approaches to strengthen the role of design in advancing Taiwan’s sustainable education agenda.